2008
DOI: 10.1017/s0954579408000321
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of child maltreatment and self-injurious behavior in a community sample

Abstract: In conjunction with prospective ratings of child maltreatment (i.e., sexual abuse, physical abuse, and physical neglect) and measures of dissociation and somatization, this study examined prospective pathways between child maltreatment and nonsuicidal, direct self-injurious behavior (SIB; e.g., cutting, burning, self-hitting). Ongoing participants in the Minnesota Longitudinal Study of Parents and Children (N = 164; 83 males, 81 females) completed a semistructured interview about SIB when they were 26 years ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
147
2
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(165 citation statements)
references
References 119 publications
11
147
2
5
Order By: Relevance
“…Thus, this work supported previous research (see Ford & Gómez, in press, for a review) that suggested that maltreatment was related to self-harm. These data collected by Yates et al (2008) showed a more complex pattern than had previously been reported, and the pattern became even more complicated when gender was included. For example, exposure to interpersonal violence did not predict self-harm for men, but did for women.…”
Section: Gender Abuse History Nonsuicidal Self-injury and Attemptementioning
confidence: 57%
See 2 more Smart Citations
“…Thus, this work supported previous research (see Ford & Gómez, in press, for a review) that suggested that maltreatment was related to self-harm. These data collected by Yates et al (2008) showed a more complex pattern than had previously been reported, and the pattern became even more complicated when gender was included. For example, exposure to interpersonal violence did not predict self-harm for men, but did for women.…”
Section: Gender Abuse History Nonsuicidal Self-injury and Attemptementioning
confidence: 57%
“…Although some theoretical and empirical models of self-harm include abuse history (e.g., Nock, 2012;Yates et al, 2008), many do not (e.g., Joiner et al, 2012;Klonsky et al, 2013). As Becker-Blease et al (2012) noted, exclusion of abuse history in empirical studies might lead to erroneous findings that, in turn, affect our ability to both prevent and understand complex phenomena.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As presented earlier, BD clinical outcomes associated with childhood maltreatment include more severe impairments in emotional self-regulation. Suicide attempts, aggressiveness, impulsivity, and mood dysregulation are independently associated with history of childhood trauma (45,46); therefore, the emergence of BD could be precipitated by these behavioral and emotional patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies in the literature reported a correlation between NSSI and socioeconomic level, being abused, problems about friendship relations, psychological disorders like depression, anxiety, behavior disorders and suicide ideation along with several risky disorders like smoking, alcohol consumption, school skipping 4,[12][13][14][15][16][17][18][19][20] .…”
mentioning
confidence: 99%